Square Stepping Exercise for Stress Management in Among Elderly: An Experimental Study - Lucya, Vita; Pratiwi, Gilang Dwi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background : Stress is a common psychological issue among older adults, particularly those residing in nursing homes. This condition can negatively affect both physical and mental health. Physical activity-based interventions, such as Square Stepping Exercise (SSE), have been explored as a potential strategy to alleviate stress in the elderly. This study aims to analyze the effect of Square Stepping Exercise on stress levels among older adults living in nursing homes. Objective: This study aims to evaluate the effect of Square Stepping Exercise (SSE) on stress levels in elderly people living in nursing homes.  Method: The method used in this research is an experiment with a pre-test and post-test design. A total of 33 elderly people in nursing homes took part in the SSE program. The stress scale was measured before and after the intervention using a measuring tool, the Perceived Stress Scale (PSS). Result: The results of the analysis show that there is a significant decrease in the stress scale after SSE training, with a p value <0.05  and Δ = 10,7. This may indicate that SSE training is effective in reducing stress levels in the elderly. This reduction in stress is associated with increased physical activity, improved balance, and social interaction during exercise. Conclusion: Square Stepping Exercise can be used as an alternative intervention to reduce stress in elderly people in nursing homes, which has a positive impact on their quality of life.